2011
DOI: 10.1364/oe.19.026936
|View full text |Cite
|
Sign up to set email alerts
|

Low-voltage high-performance silicon photonic devices and photonic integrated circuits operating up to 30 Gb/s

Abstract: We present high performance silicon photonic circuits (PICs) defined for off-chip or on-chip photonic interconnects, where PN depletion Mach-Zehnder modulators and evanescent-coupled waveguide Ge-on-Si photodetectors were monolithically integrated on an SOI wafer with CMOS-compatible process. The fabricated silicon PIC(off-chip) for off-chip optical interconnects showed operation up to 30 Gb/s. Under differential drive of low-voltage 1.2 V(pp), the integrated 1 mm-phase-shifter modulator in the PIC(off-chip) d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(26 citation statements)
references
References 35 publications
1
25
0
Order By: Relevance
“…The first designs of this type were demonstrated in 2008 [21][22][23], and since then there have been numerous versions published with different variants in the design [24][25][26][27][28][29][30][31][33][34][35][36][37]. The most straightforward form of the device has the pn junction positioned in the waveguide equidistant from the rib edges [25][26][27][28][29][30][31][32].…”
Section: Chirpmentioning
confidence: 99%
“…The first designs of this type were demonstrated in 2008 [21][22][23], and since then there have been numerous versions published with different variants in the design [24][25][26][27][28][29][30][31][33][34][35][36][37]. The most straightforward form of the device has the pn junction positioned in the waveguide equidistant from the rib edges [25][26][27][28][29][30][31][32].…”
Section: Chirpmentioning
confidence: 99%
“…1 Kim et al have demonstrated both modulators and detectors working at speeds of 30 Gb/s. 2 Just recently, IMEC announced the upcoming launch of a fully integrated 25 Gb/s platform via the ePIXfab MPW.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous and impressive works have been reported in the field of silicon photonics in recent years [1][2][3][4][5]. The advantage of silicon photonics is its compatibility with silicon microelectronic process.…”
Section: Introductionmentioning
confidence: 99%
“…Ring-resonator enhanced silicon modulators and germanium photodetectors was monolithically integrated and 3Gb/s optical link was demonstrated [1]. Higher speed off-chip/on-chip photonic interconnects was also illustrated by monolithically integrating PN depletion Mach-Zehnder modulators and Ge-on-Si photodetectors [2]. Ring modulator with improved electro-optic efficiency and Ge waveguide detector were hybrid integrated with driver circuit and receiver circuit respectively [3].Monolithic integration of the silicon photonic components and electronic circuits was performed by Luxtera [4] and IBM [5].…”
Section: Introductionmentioning
confidence: 99%